The Role of Human Resource Professional in Managing Other Salaried Professionals - Joseph A. Raelin (Career Growth and Human Resource Strategies: The Role of the Human Resource Professional in Employee Development, 1988)
The author reviews some specific ways in which human resource professionals can assist management in managing other salaried professionals.
Keywords: J24; J44; L84; M12; M53; O15; 330; Managing professionals; Human resource management; Professional development; Professional autonomy